Preservation of detrital shocked minerals derived from the 1.85 Ga Sudbury impact structure in modern alluvium and Holocene glacial deposits - Thomson, O.; Cavosie, Aaron; Moser, D.; Barker, I.; Radovan, H.; French, B. (Geological Society of America, 2014)
Detrital shocked minerals can provide valua ble residual records of eroded impact structures. Recent studies have reported shocked minerals in modern alluvium in a subtropical climate from the deeply eroded 2.02 Ga Vredefort Dome impact basin in South Africa. To evaluate the detrital shocked mineral record at a large impact structure in a temperate setting with a Holocene glacial erosional history, we investigated  4000 detrital zircons and  20,000 quartz grains at the lesseroded 1.85 Ga Sudbury Basin in Ontario, Canada, for the presence of shocked sand grains. Modern alluvium from rivers within and outside the basin, and Holocene glaciofl uvial sands (eskers and outwash deltas ) across the basin were investigated for shocked minerals. Shocked zircon and/or quartz were found in all modern rivers and most Holocene glacial deposits within, but not outside, the basin. Petrography and scanning electron microscopy (SEM; back scattered electron [BSE]; cathodoluminescence [CL]) imaging and analysis (energy-dispersive X-ray spectroscopy [EDS], electron backscatter diffraction [EBSD]) were used to document shock microstructures. Of the total detrital zircons surveyed,  3% (118/3978) were identifi ed as shocked; Holocene samples contained higher average percentages of shocked zircon (63/1361, or 4.6%, with a high of 29%) compared to modern alluvium (55/2617, or 2.1%, with a high of 6%). EBSD analysis revealed a range of shock microstructures, including planar fractures, deformation microtwins, and crystal plastic deformation. At Sudbury, detrital shocked quartz is rare compared to zircon; only 15 grains ( 0.08%) were identifi ed, all with decorated planar deformation features (PDFs). These results demonstrate that a detrital shocked mineral record exists at a large impact basin that is in a "youthful" stage of erosion, despite its age. In addition to modern alluvium, our results also identify glaciofluvial eskers and deltas as reservoirs for detrital shocked minerals; glacial episodes thus enhance the dispersal and preservation of shocked detritus in sedimentary systems. Despite physical differences, the observation that the two largest Precambrian impact basins continue to contribute detrital shocked minerals 2 b.y. after impact suggests that a shocked mineral record of impacts on early Earth should reside in Precambrian siliciclastic rocks. ©2014 Geological Society of America.